Transcriptional analysis of cell division genes in Neisseria gonorrhoeae. - Francis, Finola (University of Ottawa (Canada), 1998)
This work represents the first study of the regulation of cell division genes in the Gram negative coccus Neisseria gonorrhoeae, and this regulation was studied under aerobic and anaerobic growth conditions using two different gonococcal strains: CH811 and FA1090. Three different clusters of cell division genes were investigated: the mur-fts cluster, the ftsEX cluster, and the min cluster corresponding to homologues at the 2 min, the 78 min, and the 26 min region of the Escherichia coli chromosome, respectively. Driven by initial DNA sequencing of the pivotal cell division gene ftsZ in our laboratory, further genomic analysis using the raw data from the N. gonorrhoeae FA1090 Genome Project was used to identify the genetic organization of the mur-fts cluster as well as the min cluster. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.